2019
DOI: 10.1038/s41598-019-47622-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum enterolactone concentrations are low in colon but not in rectal cancer patients

Abstract: The dietary lignan metabolite, enterolactone, has been suggested to have anti-cancer functions, and high serum enterolactone concentrations have been associated with decreased risk of breast and prostate cancers. We hypothesized that serum enterolactone concentrations as a marker of plant-based foods are associated with decreased risk in colorectal cancer (CRC). We measured serum enterolactone glucuronide and sulfate concentrations by liquid chromatography-tandem mass spectrometry in 115 CRC patients and 76 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Após a análise dos resumos, duplicatas e artigos não correlatos à temática foram excluídos e 13 artigos foram incluídos para a etapa de análise (Tabela 1). Quanto a estratégia experimental, seis dos artigos incluídos apresentavam estudos transversais (43)(44)(45)(46)(47)(48) , dois deles estudo de coorte (11,49) , um estudo piloto (50) e quatro artigos consistiam em estudos controlados e randomizados (51)(52)(53)(54) .…”
Section: Metodologiaunclassified
See 2 more Smart Citations
“…Após a análise dos resumos, duplicatas e artigos não correlatos à temática foram excluídos e 13 artigos foram incluídos para a etapa de análise (Tabela 1). Quanto a estratégia experimental, seis dos artigos incluídos apresentavam estudos transversais (43)(44)(45)(46)(47)(48) , dois deles estudo de coorte (11,49) , um estudo piloto (50) e quatro artigos consistiam em estudos controlados e randomizados (51)(52)(53)(54) .…”
Section: Metodologiaunclassified
“…Byrd et al (2022) (52) avaliaram se dieta poderia afetar o metabolismo e a sinalização dos ácidos biliares (AB). Ocvirk S et al (2020) (45) investigaram se as diferenças nesses metabólitos podem contribuir para o alto risco de CCR em pessoas nativas do Alasca e por fim se as concentrações séricas de enterolactona como um marcador de alimentos à base de plantas estão associadas à diminuição do risco de câncer colorretal (CCR) (46) .…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…16 Although bioassays using phase II metabolites of enterolactone and enterodiol showed that their anticancer activity is moderate, 54 their locally high concentration in a free form should be possible due to the enzymatic deconjugation of circulating metabolites in the surrounding tumor associated with the ongoing inflammatory process. 99…”
Section: Lignans-enterolactone and Enterodiolmentioning
confidence: 99%